2020
DOI: 10.1111/jan.14417
|View full text |Cite
|
Sign up to set email alerts
|

A nursing informatics response to COVID‐19: Perspectives from five regions of the world

Abstract: The 21st century has seen several infectious disease outbreaks that have turned into epidemics and pandemics including Severe Acute Respiratory Syndrome (SARS) which began in Asia in 2003 (Poon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 27 publications
3
22
0
1
Order By: Relevance
“…The specialty of nursing informatics has long advocated for the integration of technology to support the profession, but it has comparatively few practitioners globally. Nursing informaticians are predominantly based in the United States, where the discipline seems to have originated, but many other countries and regions are expanding their digital nursing workforce and involvement with informatics 1112…”
Section: Challenges Persistmentioning
confidence: 99%
“…The specialty of nursing informatics has long advocated for the integration of technology to support the profession, but it has comparatively few practitioners globally. Nursing informaticians are predominantly based in the United States, where the discipline seems to have originated, but many other countries and regions are expanding their digital nursing workforce and involvement with informatics 1112…”
Section: Challenges Persistmentioning
confidence: 99%
“…La pandemia por el COVID-19 exige una acción urgente y necesaria para transformar la prestación de los servicios de salud, para expandir los programas e iniciativas de teleenfermería y de enfermería a distancia en todo el mundo (27) . Especí camente, la telesalud se utilizó para monitorear el estado de salud de las poblaciones y disminuir el número de personas que acceden a los centros de salud locales, con la participación de muchos enfermeros informáticos durante el proceso (28) .…”
Section: Desarrollo De Capacidades En Tiempos De Covid-19unclassified
“…Although some applications can provide assistance in terms of real-time information on prognosis and treatment effectiveness in some areas of health care, health experts have been concerned about patient safety (McGreevey et al 2020 ). Recent studies have indicated that health organisations have intensified their collaboration with the technology industry to scale up digital solutions for health professionals, patients and their families and capitalise on existing social media and health applications to reach key stakeholders quickly, such as at-risk vulnerable groups (Atique et al 2020 ; Tiirinki et al 2020 , p. 660). A pandemic can accelerate the digitalisation of health care, but not all consequences are necessarily predictable or positive from the perspectives of patients and professionals.…”
Section: Introductionmentioning
confidence: 99%